Illegal gambling: measuring the market using the MIMIC model. Issue 11 (2nd November 2022) - Monarca, Umberto; Cassetta, Ernesto; Rubina Nava, Consuelo; Pittiglio, Rosanna
ABSTRACT: Using a multiple indicators and multiple causes (MIMIC) model, this paper estimates the extent of illegal gambling in Italian regions over the period 2013–18. By treating illegal gambling as an unobserved latent variable directly related to its causes and effects, this model gives information about the relationship between cause and indicator variables and the latent variable from covariance structures. From the analysis, it emerges that the share of illegal gambling increases with the value of the winnings paid; it decreases when the number of authorized machines increases. We also find that individuals with low levels of education and low income show a greater propensity to gamble illegally.